Perancangan Aplikasi Voice Chat dengan Socket Programming pada Android untuk Jaringan Lokal - Allyza Nanda Purwari; Nugroho Suharto; Abdul Rasyid (Jurnal Jaringan Telekomunikasi, 2020)
Voice chat application is an application designed to replace the HT function on an Android smartphone. Besides being able to make voice calls, this application can be used to communicate with text. This application does not require cellular networks to communicate, simply by connecting to a network provided by an existing access point. The applications can be used without using a cellular network, when making an application requires a socket. Socket is an API that exists on Android studio software. While socket programming is a way to use socket components to create an application, one of which is a voice chat application. After being installed in android smartphones, each smartphone is connected to a network provided by an existing access point so that it can communicate by voice or text. Communication is carried out between smartphones with one another point to point. The test results can be concluded that this application can be used to communicate with voice and text, as long as the user is on the same network. This application can be used in all types of Android mobile phones for voice communication but communication with text can only be used on certain mobile brands.